Influence of feed rate on the dynamic properties of thin-walled partduring end-milling - Dyadya, Sergei; Kozlova, Olena; Brukhno, Eduard; Yakhno, Denys; Karamushka, Daria (Національний технічний університет "Харківський політехнічний інститут", 2024)
When selecting cutting modes for end-milling of thin-walled parts from hard-to-machine materials, their influence on machining stability must be considered. To do this, it is necessary to understand the types of vibrations that operateand the conditions under which they arise. Research has shown that different types of vibrations operatesequentially during cutting and only for a certain of time. During end-milling, forced and accompanying free oscillationsoperates due to the short duration of cutting. Their influence on the stability of the cutting process depends on the speed zone in which the milling takes place. The most unfavorable is the third speed zone of vibrations, where accompanying free vibrations of high intensity occur. Cutting speeds for machining parts from hard-to-machine materials fall precisely within this zone.The intensity of vibrations is influenced by the dynamic properties of the part. During end-milling of thin-walled parts, these properties are characterized by the amplitude and frequency of accompanying free vibrations, which exceed the natural frequency of the part's free vibrations. In other words, cutting modes alter the dynamic properties of the part.

При призначенні режимів різання для кінцевого фрезерування тонкостінних деталей з важкооброблюваних матеріалів треба враховувати їх вплив на сталість обробки. Для цього треба знати, які види коливань діють і за яких умов вони виникають. Виконаними дослідженнями встановлено, що при різанні різні види коливань діють послідовно і тільки певний час. При кінцевому фрезеруванні через короткочасність різання виникають вимушені та супроводжуючі вільні коливання. Їх вплив на сталість процесу різання залежить від того, в якій швидкісній зоні коливань буде проходити фрезерування. Найбільш несприятливою є третя швидкісна зона коливань. Тільки в ній діють супроводжуючі вільні коливання великої інтенсивності. Швидкості різання для обробки деталей з важкооброблюваних матеріалів припадають саме на цю зону. На інтенсивність коливань впливають динамічні властивості деталі. При кінцевому фрезеруванні тонкостінних деталей вони характеризуються амплітудою та частотою супроводжуючих вільних коливань, які більше за частоту вільних коливань деталі. Тобто режими різання змінюють динамічні властивості деталі.
Вплив подачі на динамічні властивості тонкостінної деталі при кінцевому фрезеруванні
Keywords: milling; thin-walled part; feed rate; oscillogram; oscillations; aviation manufacturing industry; фрезерування; тонкостінна деталь; осцилограма; коливання; якість поверхні; точність